Anthropolinguistics and Sociolinguistics: A Systematic Literature Review of Language, Culture, Identity, and Social Variation: English - Sun Jiaze; Robert Sibarani; Mhd. Pujiono; Zulfadli (Asian Multidisciplinary Research Journal of Economy and Learning, 2026)
This systematic integrative review clarifies how anthropolinguistics and sociolinguistics can be combined without erasing their distinct explanatory orientations. Literature was identified through Google Scholar, Crossref Metadata Search, publisher platforms, Indonesian scholarly repositories, author profiles, and backward citation tracing. The search record was updated on 22 July 2026 and covered works published from 1960 to July 2026. Of 31 candidate records, four duplicates were removed, 27 records were screened, 21 full-text scholarly works were assessed, and 18 works were retained at the eligibility stage. Seventeen substantive works entered thematic synthesis; the PRISMA 2020 statement was used solely as reporting guidance. Sources were coded by disciplinary orientation, unit of analysis, treatment of culture and variation, mechanism of social meaning, evidence type, and empirical relevance. Five clusters emerged: ethnography of communication, variationist sociolinguistics, indexicality and identity, language ideology, and anthropolinguistic research on oral tradition and local wisdom. The synthesis demonstrates that anthropolinguistics explains culturally situated meaning, whereas sociolinguistics establishes the patterned social distribution of linguistic forms. Indexicality connects distribution to interactional identity work, and language ideology explains the institutional evaluation of linguistic resources. The article develops a culture-variation-indexicality framework organised by cross-level traceability: each substantive claim must connect an identifiable linguistic feature, its cultural interpretation, its social patterning, and the interactional mechanism through which it acquires social meaning. The framework offers a rigorous basis for empirical studies of Indonesian multilingualism, ritual discourse, local knowledge, linguistic landscapes, and intergenerational language change.